Intervensi Ekstrak Daun Moringa oleifera, Cyclea barbata, Centella asiatica untuk Meningkatkan Perkembangan Fetus dan Kadar Protein Darah pada Model Mencit Bunting dengan Malnutrisi: Moringa oleifera, Cyclea barbata, Centella asiatica Leaves Extract Intervention Ability to Improve Fetus Development and Blood Protein Levels in Malnutrition Pregnant Model Mice - Christyaningsih, Juliana; Hatijah, Nur; Halimah, Husnul (Amerta Nutrition, 2024)
Background: Pregnant women experiencing chronic energy deficiency are at risk of giving birth to low birth weight and premature (stunted) babies. Objectives: In an effort to prevent stunting, the study investigates the effects of a 1:1:1 ratio of Moringa oleifera, Cyclea barbata, and Centella asiatica leaf extract on fetal growth and blood protein levels. Methods: This research used a laboratory experimental approach with 25 adult female Mus musculus Balb/C mice as a model of malnourished pregnancy, was divided into 5 groups: pre-test, positive control, negative control, placebo and test group. Moringa oleifera, Cyclea barbata, and Centella asiatica leaf extracts are administered to the test group and positive control in 1:1:1 ratio. Results: The study results indicated that in pregnant mice without malnutrition receiving a mixture of Moringa oleifera, Cyclea barbata, and Centella asiatica leaf extracts, the average fetal body length was 9.7% higher and their weight was 7.4% heavier than pregnant mice with experiencing chronic energy deficiency. Conclusions: The administration of Moringa oleifera, Cyclea barbata, and Centella asiatica leaf extract can contribute to improving fetal development and blood protein levels. However, its effectiveness is more pronounced in normal pregnancies than in pregnancies with chronic energy deficiency as it can prevent stunting.